Review of Accountability Across Procurement, Energy Performance Contracting, and Measurement and Verification in Public Building Decarbonization - Haluk Yaman; Berkay Gür (Buildings, 2026)
Background: Public building decarbonization is accountable only when procurement requirements remain traceable through contractual obligations and post-implementation verification. Objective: This review mapped that chain across procurement and life-cycle appraisal (Stage A), energy performance contracting and energy service company arrangements (Stage B), and measurement and verification (Stage C). Methods: Scopus and Web of Science searches were executed with a broad audit range, while the final primary eligibility window was restricted to English-language publications from 2020 through to 13 August 2026. Citation and targeted methods supplemented the database stream, and two authors verified full-text eligibility, study family assignments, stage codes, principal outcomes, and candidate complete chains. Results: Thirty-five reports representing 33 study families were included in the final synthesis. Stages A, B, and C were reported by 15, 17, and 11 families, respectively. One family contained all three stages and was also the sole strict same-project chain (3.0%); it reported performance-linked settlement. Twenty-two families were model- or method-prospective, four were contract-, programme-, or document-based, six reported measured or adjusted operational evidence, and one reported an externally verified programme. Conclusions: The current literature shows substantial technical and contractual activity but limited same-case continuity. PBDAF is, therefore, presented solely as a review-derived conceptual reporting proposal for standardized reporting and prospective testing; it is not a validated scoring or diagnostic instrument.